Effect of winter and spring planting time on yield and yield components of chickpea at dry land conditions - Naser Majnoun Hosseini; Reza Hamzeii (پژوهش‌های حبوبات ایران)
In order to evaluate a better sowing date of chickpea cultivars in dry land conditions, a factorial experiment in randomized complete block design with four replications was carried out at research station of Bahar (Hamadan province) during 2005-2006 cropping season. Two planting time included winter and spring and four chickpea cultivars (cvs.) including one local (check) and three improved cvs. (i.e. Arman, Hashem and ILC482) were used. Plant characteristics such as seedling establishment percentage, plant height, first node height, number of primary branches, pods per plant, seeds per pod, 100 seed weight, biological yield, seed yield and harvest index were recorded. The results showed significant differences among sowing dates and chickpea cvs. The interaction effects was significant for all traits except for plant height, first node height, primary branches, seeds per pod and 100 seed weight. Mean seed and biological yield of cv. ILC482 were higher compared to other cultivars and were 1045 and 2385 kg.ha-1, respectively. The correlation coefficient between seed yield and total dry matter accumulation (r= 0.57**) and harvest index) r= 0.74 (**was significant. The relationships between seedling establishment percentage and dry matter accumulation (r = 0.67**) revealed that the lower seed yield of winter dry land chickpea in this region was due to lower seedling establishment (emergence). Therefore, the winter dry land chickpea that produced higher seed and dry matter accumulation as compared to spring planting in Bahar region of Hamadan province was most likely due to accessibility of cold tolerance cvs. (ILC482).Key words: Biological yield, Dry land chickpea, Planting dates, Seedling establishment, Seed yield